Quand un conte se fait roman L’Ogre de Grand Remous de Robert Lalonde - Jarosz, Krzysztof (Romanica Silesiana)
The article concentrates on the problem of intertextuality in Robert Lalonde’s “L’Ogre de Grand Remous”, based on Charles Perrault’s fairy tale “Tom Thumb” and the motto to Jean Giono’s “Deux cavaliers de l’orage”. The author argues that Lalonde’s novel is a pretext to present the problems of modern times and cultural references to Quebecness, Americanness and Europeanness. Key-words: Robert Lalonde; Fairy-Tale; intertextuality; contemporary national identities